2019
DOI: 10.1002/ece3.5493
|View full text |Cite
|
Sign up to set email alerts
|

Bird species diversity in Altai riparian landscapes: Wood cover plays a key role for avian abundance

Abstract: Aims We aim to understand bird richness and variation in species composition (beta diversity) along a 630 km riparian landscape in the Altai Mountains of China and to test whether vegetation cover is the main explanation of species diversity. Methods We selected nine regions along a gradient of natural vegetation change. Bird surveys and environmental measurements were conducted at 10 points in each of the nine regions. We collected environmental land cover variables such as wood cover (area proportion of tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Based on a literature review, we identified and measured 15 environmental variables related to vegetation structure and human presence (Table 1). These variables are known to influence bird communities (Alaya‐Ltifi & Selmi, 2014; Hanane et al, 2019; Jakobsson & Lindborg, 2017; Li et al, 2019; Mahmoudi et al, 2016; Söderström et al, 2001; Wiacek et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a literature review, we identified and measured 15 environmental variables related to vegetation structure and human presence (Table 1). These variables are known to influence bird communities (Alaya‐Ltifi & Selmi, 2014; Hanane et al, 2019; Jakobsson & Lindborg, 2017; Li et al, 2019; Mahmoudi et al, 2016; Söderström et al, 2001; Wiacek et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, several works investigated the effect of habitat type and quality on the richness and diversity of birds (Jacoboski, Mendonça‐Lima, & Hartz, 2016; Marsden, Whiffin, & Galetti, 2001; Proenca, Pereira, Guilherme, & Vicente, 2010; Zurita, Rey, Varela, Villagra, & Bellocq, 2006). The local vegetation structure, for instance, (a) tree and shrub density/cover (Jakobsson & Lindborg, 2017; Li et al, 2019; Söderström et al, 2001), (b) plant species richness (Baláž & Balážová, 2012; Šálek, Svobodová, & Zasadil, 2010) and (c) canopy height (Robbins, 1980), often contributes to increasing the richness and diversity of birds. The difference in habitat type may also affect the bird diversity such as when comparing natural forests to artificial plantations (Hanane, Cherkaoui, Magri, & Yassin, 2019; Marsden et al, 2001; Zurita et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high diversity and species richness of birds in the Dokima forest emphasizes the importance of implementing conservation measures and limiting human activity in the area according to different bird threat factors. For the sake of conserving high bird diversity in the entire riparian landscape, the wood cover, which includes trees, bushes, and young saplings, should be maintained, not only trees [ 48 ]. The forest patch and its environs are important for bird habitats [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study of avian diversity, corresponding to their feeding guilds plays an important role in understanding the complexity of ecosystem structure and also provides information on different types of habitats (Azman et al, 2011). Knowledge of feeding guild is important for improving effectiveness in maintaining bird diversity (Li et al, 2019). Variation in vegetation structure affects the distribution of bird diversity and their feeding guilds (Pearman, 2002).…”
Section: Introductionmentioning
confidence: 99%